Pengaruh Disiplin, Komitmen Dan Kompensasi Terhadap Kinerja Karyawan (CT. Pictures Tulungagung) - Udya Alibya Rikaz Ulul Azmi; Ahmad Jauhari; Diana Ambarwati; Lina Saptaria (Pusat Riset dan Inovasi Nasional, 2023)
This study discusses the effect of work discipline, organizational commitment, compensation on employee performance at CT. Pictures Tulungagung, this study aims to determine and explain the results of the effect of work discipline, organizational commitment, compensation on employee performance at CT. Pictures Tulungagung. The method used in this research is descriptive quantitative. The population used in this study were all employees who worked at CT. Pictures Tulungagung. The sample used in this study were all CT employees. Pictures Tulungagung with 33 employees. The sampling method used in this study used saturated sampling. The result of this study is that work discipline has a partial effect on employee performance with a significant value of 0.000 <0.05. Organizational commitment has a partial effect on employee performance with a significant value of 0.003 <0.05. Compensation has a partial effect on employee performance with a significant value of 0.012 <0.05. Work discipline, organizational commitment, compensation simultaneously affect employee performance with a significant value of 0.000 <0.05.